A Feminist Semiotic Study on the Symbolic Meaning of Femininity in the Book Cover Design: There’s a She-Wolf Inside Every Woman - Ainal Husna; Juwita Wirta Sri Depi; Amelia Isti Fahmi (Melayu Arts and Performance Journal, 2025)
This study explores the symbolic meaning of femininity embedded within the visual elements of the book cover "Ada Serigala Betina dalam Diri Setiap Perempuan" (There’s a She-Wolf Inside Every Woman) through a feminist semiotic lens. Utilizing Roland Barthes' theory of semiotics, the research analyzes the cover’s color palette, illustrations, typography, and layout, all of which visually represent the identity, power, and resistance of women from a cultural feminist perspective. The dominant use of pastel purple signifies not just aesthetic softness, but a deeper connection to the Suffragette movement, highlighting resistance and spiritual strength. The illustration of multiple women without facial detail, accompanied by the shadow of a howling she-wolf, reflects the rejection of conventional beauty standards and emphasizes the inner strength and diversity of women’s identities. Bold sans-serif typography reinforces the assertive message of empowerment. The study concludes that the book cover is not merely a promotional medium, but a visual discourse that deconstructs patriarchal norms and amplifies feminist ideology through symbolic and inclusive design. Ultimately, the book cover functions as a communicative artifact that embodies the collective journey and struggle of women within a patriarchal framework.